Researching Adult Literacy Learners’ Lives: Journeys of Trauma Toward Transformation - Karen Magro (Adult Education Research Conference, 2004)
This qualitative study used autobiographies and self-report inventories to explore ten adult literacy learners’ motivation for returning to school, their experiences at school, and the barriers that most interfered with their ability to complete their studies. Another key aim of the study was to investigate the characteristics of teachers, curriculum preferences, and teaching and learning strategies that either hindered or enhanced individuals’ ability to learn